DIPEPTIDYL PEPTIDASE-IV INHIBITORY ACTIVITIES OF MEDICINAL PLANTS: TERMINALIA ARJUNA, COMMIPHORA MUKUL, GYMNEMA SYLVESTRE, MORINDA CITRIFOLIA, EMBLICA OFFICINALIS - Borde, Manjusha K; Suman, Rajesh Kumar; Mohanty, Ipseeta Ray; Deshmukh, Y A (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The present study was designed to screen the dipeptidyl peptidase-IV (DPP-IV) inhibitory ability of hydroalcoholic extracts of Terminalia arjuna, Commiphora mukul, Gymnema sylvestre, Morinda citrifolia, and Emblica officinalis and compare their inhibitory activity with the synthetic DPP-IV inhibitors (Sitagliptin and Vildagliptin). The aim of the study was to identifying indigenous sources of DPP-IV inhibitors for the management of type II diabetes mellitus as alternatives to their synthetic counterparts. Methods: The hydroalcoholic extract of T. arjuna, C. mukul, G. sylvestre, M. citrifolia, E. officinalis and synthetic DPP-IV inhibitors (Sitagliptin and Vildagliptin) were tested in vitro for DPP-IV inhibitory activity. Results: The DPP-IV inhibitory activity of synthetic drugs Vildagliptin was found to be 90.42±7.84% and Sitagliptin 84.67±8.21%. The DPP-IV Inhibitory activity of T. arjuna was found to be 83.39±7.58%, C. mukul: 92.97± 8.45%, G. sylvestre: 16.98±1.69%, M. citrifolia: 24.64±2.24%, and E. officinalis: 85.95±7.16%. C. mukul extract showed superior inhibitory activity than reference standard drugs (Sitagliptin and Vildagliptin). Conclusion: C. mukul, T. arjuna, and E. officinalis extracts possess significant DPP-IV Inhibitory activity while G. sylvestre and M. citrifolia failed to markedly inhibit DPP-IV enzyme. Keywords: Type II diabetes mellitus, Dipeptidyl peptidase-IV inhibitors, Plant extracts, In vitro assay.